The unwritten rules of friendship : simple strategies to help your child make friends - Elman, Natalie Madorsky; Kennedy-Moore, Eileen (Boston : Little, Brown, 2003)
Discusses the unwritten rules of social situations children need to know in order to make and keep friends, offers advice to parents and other adults on how to assess a child's social skills, and describes strategies for helping children develop social relationships.
Includes bibliographical references (p. [317]-324) and index.
Library Journal.
Adult
Keywords: Child rearing; Friendship in children; Social skills in children; Child rearing; Friendship in children; Social skills in children